A first revision of the Italian Ecoregion map. (2nd November 2018) - Blasi, Carlo; Capotorti, Giulia; Copiz, Riccardo; Mollo, Barbara
Abstract: According to advances in phytogeographic knowledge, a revision of boundaries for the Italian Ecoregions have been made. Main changes relate to the southern and eastern limits between Temperate and Mediterranean Divisions. The revision triggered a comprehensive update of Ecoregions for an improved support to biodiversity and sustainable management initiatives.